The Critical Role of Adolescent Girls’ Adherence to Taking Blood Supplement Tablets as A Key to Preventing Early Stunting - Islaeli Islaeli; Ari Nofitasari; Asbath Said; Sartini Risky; Islamiyah Islamiyah; Anisa Purnamasari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Anemia is a common health problem in adolescent girls that risks causing complications during pregnancy and stunting in children. Blood supplementation tablets are an effective intervention, but the compliance of adolescent girls in consuming them is still low. Objective: This study aimed to analyze adherence to taking blood supplement tablets in adolescent girls. Methods: With a mixed-method design and involving 124 respondents from a total population of 180 adolescent girls, this study used simple random sampling and chi-square statistical analysis to assess the relationship between knowledge variables and the role of parents, as well as in-depth interviews to assess the role of health workers and schools. Results: The results showed that there was a significant association between knowledge (p < 0.001) and parental role (p 0.001) with the compliance of adolescent girls in taking blood supplement tablets. Interview findings also revealed that health workers and schools distribute blood supplement tablets every month to support efforts to increase adherence. Conclusion: knowledge, parental support, and the active role of health and school personnel play an important role in improving the adherence of adolescent girls to taking blood supplement tablets. It is recommended that all parties, especially parents and schools, collaborate to improve adolescents' understanding and adherence to taking blood supplement tablets.